Knowledge meaning and management in requirements engineering. Issue 3 (June 2017) - Serna M., Edgar; Bachiller S., Oscar; Serna A., Alexei
Highlights: What is the meaning of knowledge in requirements engineering? What approaches are proposed to manage knowledge in requirements engineering? Can the efficiency and the efficacy of knowledge management models be evidenced in requirements engineering? The knowledge management used to construct the requirements specification should be performed in a structured manner to discover, analyze and understand the data–information–knowledge chain. Abstract: It is traditionally assumed that requirements specification, as a product of requirements engineering, has a high impact on the ensuing software development stages. Therefore, the knowledge management used to construct the requirements specification should be performed in a structured manner to discover, analyze and understand the data–information–knowledge chain, both tacit and explicit, that the interested parties possess. In this article, the results of a literature review are presented, seeking to answer the following questions: (1) What is the meaning of knowledge in requirements engineering? (2) What approaches are proposed to manage knowledge in requirements engineering? (3) Can the efficiency and the efficacy of knowledge management models be evidenced in requirements engineering? Thirty-six works were chosen for analysis out of a total 83 found in our search. The analysis showed that (1) knowledge has a central significance at this stage, but the authors have yet to agree on the best methods to impart and apply that knowledge; (2) no general framework has emerged as a validated approach to manage knowledge for requirements engineering; and (3) the evaluation marks for model efficiency and efficacy are low, consisting mostly of personal interpretations.